2016
DOI: 10.1007/s10729-015-9352-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nurse capacity in a teaching hospital neonatal intensive care unit

Abstract: Patients in intensive care units need special attention. Therefore, nurses are one of the most important resources in a neonatal intensive care unit. These nurses are required to have highly specialized training. The random number of patient arrivals, rejections, or transfers due to lack of capacity (such as nurse, equipment, bed etc.) and the random length of stays, make advanced knowledge of the optimal nurse a requirement, for levels of the unit behave as a stochastic process. This stochastic nature creates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is suggested that these are the predominant reasons accounting for the increasing trend for stochastic approaches in research papers compared to deterministic ones as seen in Figure 5. Many of the papers use both stochastic and deterministic approaches, generally using stochastic simulation to evaluate and test the deterministic approach [17,99,103,[121][122][123][124][125][126][127][128]. When commenting on research trends, Madell, Villa, Hayward and Comte [89] observed that the increased computational complexity inherent with these types of questions explains the current trend of researchers to focus on deterministic approaches.…”
Section: Research Gapsmentioning
confidence: 99%
“…It is suggested that these are the predominant reasons accounting for the increasing trend for stochastic approaches in research papers compared to deterministic ones as seen in Figure 5. Many of the papers use both stochastic and deterministic approaches, generally using stochastic simulation to evaluate and test the deterministic approach [17,99,103,[121][122][123][124][125][126][127][128]. When commenting on research trends, Madell, Villa, Hayward and Comte [89] observed that the increased computational complexity inherent with these types of questions explains the current trend of researchers to focus on deterministic approaches.…”
Section: Research Gapsmentioning
confidence: 99%
“…Managing an optimum resource configuration is difficult for many countries, owing to increased demand and limited hospital resources [34][35][36][37][38][39][40][41]. Researchers have used simulation and optimisation techniques to generate optimum resource profiles for a given scenario.…”
Section: Generating Optimum Resource (Bed/staff) Configurationsmentioning
confidence: 99%
“…Kokangul et al [38] focus on nurse capacity in this regard. In these units, responsibility for the care of newborns, equipment, and employee capacity is very important.…”
Section: Generating Optimum Resource (Bed/staff) Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals crowding problem is defined in detail (context, causes, effects […]) by many works (Jebbor et al , 2018), (Boyle et al , 2012) and (Casalino et al , 2013). Works dealing with this problem focus their studies either on human resources (de Bruin et al , 2010), (Beeknoo and Jones, 2016), (Green and Liu, 2015), (Boulton et al , 2016) and (Kokangul et al , 2017) or material resources (Izady and Worthington, 2012), (Zeltyn et al , 2011), (Green et al , 2006), (Vass and Szabo, 2015) and (Bekker et al , 2017). Only few ones study both resources types, but separately (without being combined) (Mital, 2010).…”
Section: Related Literaturementioning
confidence: 99%